Upaya Meningkatkan Hasil Belajar IPA Menggunakan Model Pembelajaran Project-Based Learning pada Siswa Kelas V Di SDN-11 Palangka - Wila; Rumiati; Tribuani (Pusat Kajian Bahasa Daerah & Budaya, 2024)
This study used the Classroom Action Research method which was carried out in two cycles with the aim of determining the effectiveness of using a project-based learning model in improving the learning outcomes of science subject in the fifth-grade students of SDN-11 Palangka, Kota Palangka Raya. This study was based on observation and interview with a classroom teacher at the school where researchers found problem in student learning outcomes. One of problems is that there were still many students who have not mastered the learning material of the science subject because the average score achieved was 70.4 where this score is still below the Minimum Completeness Criteria (KKM) standardized by the school, which is 75. To solve the problem, researchers tried to use the project-based learning model as a solution. The results showed that the teacher's activity score increased from cycle I to cycle II with the achievement criteria from the category of